Plasma Complement C1q/tumor necrosis factor-related protein 15 concentration is associated with polycystic ovary syndrome - Akram Vatannejad; Reza Fadaei; Fouzieh Salimi; Fatima Zahraa Fouani; Behnam Habibi; Somayeh Shapourizadeh; Samira Eivazi; Sadegh Eivazi; Asie Sadeghi; Nariman Moradi (PLoS ONE, 2022)
Polycystic ovarian syndrome (PCOS) is a common poignant endocrine disorder affecting women, posing a close association with metabolic syndrome and obesity. Existing literature characterizes PCOS with deranged levels of several adipokines and myokines. CTRP15 is a paralogue of adiponectin, mainly expressed by skeletal muscles, and plays a key role in insulin, glucose, and lipid metabolism. In the current study, we aim to determine the circulating levels of CTRP15 and evaluate its association with cardiometabolic and inflammatory parameters in PCOS women. This case-control study included 120 PCOS patients (60 Recurrent pregnancy loss (RPL) and 60 infertile (inf) PCOS) and 60 healthy non-PCOS controls. Serum levels of hs-CRP were measured by commercial kits, while serum levels of adiponectin and CTRP15 were determined using the ELISA technique. Serum levels of CTRP15 were significantly elevated in PCOS-RPL and PCOS-inf subgroups when compared to controls (94.80 ± 27.08 and 87.77 ± 25.48 vs. 54.78 ± 15.45, both P < 0.001). Moreover, serum adiponectin was considerably lower in the PCOS group and subgroups (P < 0.001), while serum hs-CRP, fasting insulin, HOMA-IR, and free testosterone were significantly higher when compared to the non-PCOS group (P < 0.05). Furthermore, CTRP15 closely associated with FSH, HOMA-IR, hs-CRP, and BMI. These results highlight a possible involvement of CTRP15 in the pathogenesis of PCOS. The elevated levels of CTRP15 might be a compensatory mechanism for the metabolic dysregulations (excess adiposity, insulin resistance, metaflammation) associated with the syndrome. Nevertheless, future studies are necessary to unravel the underlying mechanism.